PENGARUH KONSENTRASI NaCl DAN RASIO AIR DENGAN BAHAN TERHADAP KARAKTERISTIK MUTU PATI UBI GADUNG (Dioscorea hispida Dennst) - Desi Rastiyati, Ni Luh; Hartiati, Amna; Admadi, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September, 2016)
This study aims to 1) know the effect of NaCl concentration and the ratio of water to the material of the quality characteristics of potato tuber gadung, 2) knowing the quality characteristics of best potato tuber gadung made from the effect of NaCl concentration and the ratio of water to material. This study uses a randomized block design factorial design. The first factor is the soaking using NaCl solution that consists of three levels: NaCl 0%, NaCl 5%, NaCl 10% and the second factor is ratio of water and tuber gadung peel which consists of 3 levels: 2: 1, 4: 1, 6 : 1,. Each treatment was divided into two by the time of implementation. Variables observed were yield, ash content, moisture content, starch content, amylose content, amylopectin content and multiple comparison test colors. Determining the best treatment is done by testing the effectiveness index. The effect of NaCl concentration and the ratio of water to material and their interactions very significant effect on the quality characteristics of starch tuber on the yield and comparison plural color test (Degrees white), while the quality characteristics of starch tuber gadung not significantly affect the ash content, moisture content, starch content, levels of amylose and amylopectin content. Starch with soaking treatment in 10% NaCl solution and ratio of water and tuber gadung 6: 1 with the quality characteristics of the best gadung starch tuber is, has a yield of 17.17% and a comparison plural color test 4.95% (equal whiteness of R), levels ash 0.18%, the water content of 5.46%, 45,91% starch content, amylose content was 0.17% and 45,74% amylopectin content Keywords: NaCl, ratio water, starch, tuber gadung.
Keywords: 112